Oxidized Lipids: Common Immunogenic Drivers of Non-Alcoholic Fatty Liver Disease and Atherosclerosis - Hoebinger, Constanze; Rajcic, Dragana; Hendrikx, Tim (Frontiers in Cardiovascular Medicine, 2022)
The prevalence of non-alcoholic fatty liver disease (NAFLD), ranging from simple steatosis to inflammatory steatohepatitis (NASH) and cirrhosis, continues to rise, making it one of the major chronic liver diseases and indications for liver transplantation worldwide. The pathological processes underlying NAFLD not only affect the liver but are also likely to have systemic effects. In fact, growing evidence indicates that patients with NAFLD are at increased risk for developing atherosclerosis. Indeed, cardiovascular complications are the leading cause of mortality in NAFLD patients. Here, we aim to address common pathophysiological molecular pathways involved in chronic fatty liver disease and atherosclerosis. In particular, we focus on the role of oxidized lipids and the formation of oxidation-specific epitopes, which are important targets of host immunity. Acting as metabolic danger signals, they drive pro-inflammatory processes and thus contribute to disease progression. Finally, we summarize encouraging studies indicating that oxidized lipids are promising immunological targets to improve intervention strategies for NAFLD and potentially limit the risk of developing atherosclerosis.